Psychological and pedagogical aspects of the formation of practical knowledge in the study of the course "Technical Mechanics" - Suyunova Yulduz Akhmatovna (Zien Journals, 2022)
In the field of professional motivation, a positive attitude of the student to the chosen profession plays a crucial role, since this is due to the final goals of education. A positive attitude to the profession determines the formation of other private motivations in harmony with sufficient knowledge of this profession
Keywords: technical; mechanics; practical; knowledge